2023
DOI: 10.1155/2023/7161091
|View full text |Cite
|
Sign up to set email alerts
|

Stevia rebaudiana Methanolic Leaf Extract in Egypt: Phytochemical Analysis, Antioxidant, Antilipid Peroxidation, Antihemolytic, Antimetastatic, and Anticancer Properties

Abstract: The phenolic and flavonoid content of the Stevia rebaudiana hydromethanolic extract (SRHME) was examined, and phytochemical identification using GC-mass spectrometry was achieved. Also, the antioxidant, antihemolytic, and antilipid peroxidation capabilities of the extract were assessed. The extract’s potential to induce apoptosis, inhibit cell proliferation, and reduce metastasis in SKVO3 cells was also checked. The findings of the GC-MS chromatogram demonstrated the existence of bioactive antioxidants and ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 107 publications
(99 reference statements)
0
11
0
Order By: Relevance
“…It was shown that a sizable portion of the cells were created in the S phase, suggesting that apoptosis was initiated and that the cell cycle was stopped at that point. This result demonstrates that compound 49 therapy is effective in stopping the growth of cancer cells and can disturb normal cell cycle progression [66,67].…”
Section: Anticancer Activitymentioning
confidence: 79%
“…It was shown that a sizable portion of the cells were created in the S phase, suggesting that apoptosis was initiated and that the cell cycle was stopped at that point. This result demonstrates that compound 49 therapy is effective in stopping the growth of cancer cells and can disturb normal cell cycle progression [66,67].…”
Section: Anticancer Activitymentioning
confidence: 79%
“…These kinds of proteins control the cell cycle by modulating the functions of complexes made up of cyclins and cyclin-dependent kinases (CDKs). For instance, CDK2/cyclin inhibition can trigger S-phase progression delays [30]. One of the most important strategies for halting the expansion of cancer cells is to disrupt their normal cell cycle progression [30].…”
Section: Examining the Cell Cyclementioning
confidence: 99%
“…For instance, CDK2/cyclin inhibition can trigger S-phase progression delays [30]. One of the most important strategies for halting the expansion of cancer cells is to disrupt their normal cell cycle progression [30]. Thus, by using flow cytometry, it was probable to analyze the influence of compound 4 on the control of the MCF-7 cell cycle progression.…”
Section: Examining the Cell Cyclementioning
confidence: 99%
“…Then, the final powder of ASE was weighed and stored in clean falcon tubes at −20°C until usage as described before, 19 and it was carried out at Cairo University's Faculty of Science's Micro Analytical Centre.…”
Section: Preparation Of Aqueous Stevia Extract (Ase)mentioning
confidence: 99%
“…The atomic mass unit (AMU) range (m/z) for the MS scan was 50-550, with a solvent delay of 30 min and electron impact (EI) ionization at 70 eV. The NIST mass spectral search programme for the NIST/EPA/NIH mass spectral library Version 2.2 was used to identify the constituents by mass fragmentations, as mentioned in the previous research, 19 and it was performed at the central lab at the faculty of science at Ain Shams University.…”
Section: Characterization Of Ase Using Gas Chromatography-mass Spectr...mentioning
confidence: 99%